Female Monarchal Succession in Hellenistic and Jewish Society in Antiquity: Parallels and Contrasts - Liebowitz, Etka (Journal for the study of Judaism, 2018)
Starting with the Macedonian and Seleucid queens and continuing with the line of sovereign queens during the last 150 years of the Ptolemaic dynasty, the paradigm of a royal woman wielding power and even ascending to the throne was known and accepted in Hellenistic society. The reign of Queen Alexandra, which represents the only (successful) case of female monarchal succession to the throne in Jewish society in Antiquity, was undoubtedly influenced by this Hellenistic tradition. Based upon an analysis of Josephus’s writings and other sources, along with a critical feminist historiographical approach, this paper investigates how Jewish and Hellenistic queens resembled and differed from one another in their roles and characteristics.